2022
DOI: 10.3390/nu14214479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Inorganic Nitrate and Nitrite Supplementation on Cardiorespiratory Fitness and Skeletal Muscle Oxidative Capacity in Type 2 Diabetes: A Pilot Randomized Controlled Trial

Abstract: Nitric oxide (NO) stimulates mitochondrial biogenesis in skeletal muscle. However, NO metabolism is disrupted in individuals with type 2 diabetes mellitus (T2DM) potentially contributing to their decreased cardiorespiratory fitness (i.e., VO2max) and skeletal muscle oxidative capacity. We used a randomized, double-blind, placebo-controlled, 8-week trial with beetroot juice containing nitrate (NO3−) and nitrite (NO2−) (250 mg and 20 mg/day) to test potential benefits on VO2max and skeletal muscle oxidative capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…These findings suggest that metformin may not directly target cardiac steatosis but may achieve the effects through the modulation of gut microbiota populations. In addition to pharmaceutical interventions, the intake of dietary nitrate (NO 3 − ) through beetroot juice has been shown to enhance exercise capacity in patients with HFpEF [239] and increase the maximum rate of oxygen consumption during exercise in patients with diabetes [240]. Rodent studies demonstrated the beneficial effect of dietary nitrate on HFD-induced liver steatosis through the modulation of microbiota [241] and cardiomyopathy [242] in mice.…”
Section: Targeting Gut Homeostasismentioning
confidence: 99%
“…These findings suggest that metformin may not directly target cardiac steatosis but may achieve the effects through the modulation of gut microbiota populations. In addition to pharmaceutical interventions, the intake of dietary nitrate (NO 3 − ) through beetroot juice has been shown to enhance exercise capacity in patients with HFpEF [239] and increase the maximum rate of oxygen consumption during exercise in patients with diabetes [240]. Rodent studies demonstrated the beneficial effect of dietary nitrate on HFD-induced liver steatosis through the modulation of microbiota [241] and cardiomyopathy [242] in mice.…”
Section: Targeting Gut Homeostasismentioning
confidence: 99%
“…In relation to Type 2 Diabetes Mellitus, substantial reductions in VO2 maximum make daily activities more demanding, which reinforces the need for additional strategies that can have significant clinical implications, which include nitrate supplementation. 3 Aging contributes to reduction in NO bioavailability, with chronic supplementation of NO precursors having potential effects on vascular function and health, cerebral and muscular oxygenation and physical performance in healthy elderly people. 4 Furthermore, studies present the importance of modulating the oral and intestinal microbiota as influential for the conversion of nitrate to nitrite, affecting nitric oxide signaling and also potentially improving sports performance.…”
Section: Introductionmentioning
confidence: 99%